Colonoscopy resource availability and its association with the colorectal cancer diagnostic interval: A population‐based cross‐sectional study. (10th November 2019) - Webber, Colleen; Flemming, Jennifer A.; Birtwhistle, Richard; Rosenberg, Mark; Groome, Patti A.
Abstract: Background: Colonoscopy is a key resource used to diagnose colorectal cancer (CRC). This study evaluated the relationship between colonoscopy availability and the length of the CRC diagnostic interval. Methods: This is a cross‐sectional study of CRC patients diagnosed in Ontario, Canada, in 2008–2012. We used administrative health data to characterise colonoscopist density, private colonoscopy clinic access, distance to the closest colonoscopist and the diagnostic interval, defined as the time from patients' first cancer‐related healthcare encounter to their cancer diagnosis date. We used multivariable quantile regression to evaluate the association between colonoscopy availability and the diagnostic interval, modelling the median and 90th percentile. Results: The median diagnostic interval was 84 days (90th percentile 323 days). The diagnostic interval was longer in patients residing in areas with lower colonoscopists density or private clinic access (adjusted median difference = 9 and 19 days, respectively), with evidence of effect modification by symptom status. Increased distance to a colonoscopist was associated with a longer diagnostic interval in asymptomatic patients, but a shorter diagnostic interval in symptomatic patients (adjusted median difference = 29 and −25 days, respectively). Conclusions: This study demonstrated that reduced colonoscopy resource availability is associated with longer diagnostic intervals for CRC patients.